2022
DOI: 10.26689/jcer.v6i6.4130
|View full text |Cite
|
Sign up to set email alerts
|

Critical Information Literacy Education Strategies for University Students in the Post-Pandemic Era

Abstract: The advent of the post-pandemic era, with its risks, uncertainties, and global characteristics, puts forward urgent requirements for the innovation of information literacy education in universities. Critical information literacy has become the top priority of information literacy education. It is urgent to explore diversified and effective critical information literacy education strategies for university students. This paper mainly expounds the educational strategies of critical information literacy, such as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…They perceive their transliteracies as much more than a mere tool for communication. They represent a means to survive, to keep oneself safe, to get along, to encourage each other and to build community, and a weapon to fight back against vicious attacks against the very core of who they are [97,98].…”
Section: Transresistance: Types Components and Phases When In Motionmentioning
confidence: 99%
“…They perceive their transliteracies as much more than a mere tool for communication. They represent a means to survive, to keep oneself safe, to get along, to encourage each other and to build community, and a weapon to fight back against vicious attacks against the very core of who they are [97,98].…”
Section: Transresistance: Types Components and Phases When In Motionmentioning
confidence: 99%
“…Albitz (2007) exposed disconnects between higher education graduation goals and imparting such knowledge in preparing information literate, critical thinking students. Liao and Tian (2022) indicated that critical information literacy has become the top priority of information literacy education and will be enriched through primary material analysis, reflection, and critical reading.…”
Section: Research On Information Literacy Education For University St...mentioning
confidence: 99%
“…Bawden (2018) and Vakkari et al (2020) advocate for more empirical research to uncover the connection between information literacy skills and information behavior and the development and integration of these skills into graduate education. Additionally, investigating the most effective strategies and techniques to enhance information literacy among graduate students is warranted (Argelagos et al, 2022;Liao & Tian, 2022).…”
Section: Introductionmentioning
confidence: 99%